Prinsip dan Metode Pendidikan Anak Usia Dini - Atabik, Ahmad (THUFULA, 2015)
This article describes the principles and methods of early childhoodeducation. The first discussions will start from the understanding of children,early childhood and early childhood education principles, urgency and methodsof application. Early childhood education is education before primary educationwhich is an approach to development that is intended for children from birth tothe age of six. This education is done through the provision of education to helpthe growth stimuli entering further education, which was held in formal, nonformaland informal. In early childhood education methods are needed in order tostudy the effects and on target. Learning in early childhood requires unique andcreative methodology. The role of a teacher is needed in educating children andexplores the potential of students. From here teachers in early childhood educationis seen not only as caregivers and counselors, but the teacher is required to meetthe standards of the teaching profession. Children’s education must begin from anearly age, Islam emphasizes education begins since a child is born; it is based onthe teaching of the Prophet told his community that advocates for azan when thenew baby is born.